Plasmonic waveguides and nano-antennas for optical communications - Sallam, Mai Osama (AUC Knowledge Fountain, 2017)
The field of plasmonics has received great attention during the past years. Plasmonic devices are characterized by their small electrical size which enabled researchers to overcome the challenge of the size mismatch between the bulky photonic devices and the small electronic circuits. Plasmonic metals are characterized by their lossy dielectric nature which is different from the highly conductive classical metals. Consequently, the design of plasmonic devices necessitates upgrading the existing solvers to take into consideration their material properties at the optical frequency range. In this thesis, a plasmonic transmission line mode solver is developed in which the propagation characteristics of plasmonic transmission lines/waveguides are calculated. More specifically, the solver calculates the propagation constant, losses, and mode profile(s) of the propagating mode(s). The transmission lines can have any topology and are assumed to be placed within a stack of flat layers. The solver is developed using the Method of Moments technique which is characterized by its tremendously decreased number of unknowns compared to the finite element/difference methods leading to much faster calculation time. The solver is tested on several plasmonic transmission lines of various topologies, number of metallic strips and/or surrounding media. These transmission lines include rectangular strip, circular strip, triangular strip, U-shaped strip, horizontally coupled strips, and vertically coupled strips. The obtained results are compared with those calculated by the commercial tool â€œCSTâ€. Very good agreement between both solvers is achieved. The second line presented within this thesis is concerned with the design of plasmonic wire-grid nano-antenna arrays. The basic element of this array is a nano-rod, whose propagation characteristics are first obtained using the developed solver. The arrays are then optimized using â€œCSTâ€. Within the context of this thesis, three nano-antenna arrays are proposed: a five-element wire-grid array, an eleven-element wire-grid array, and a novel circularly polarized wire-grid array. All of these arrays have high directivity and are suitable for inter-/intra-chip optical communication, where they replace the losing transmission lines.